LEGAL VACANCY IN PROTECTION OF VICTIMS OF PERSONAL DATA MISUSE FOR FICTITIOUS BANKING CREDIT - Azis, Miftakul; Fakrulloh, Zudan Arief (International Journal of Social Service and Research, 2024)
Personal data have become a critical issue in the era of global connectivity, where the use of mobile devices such as smartphones and tablets connected to the internet has created an increasingly complex communication network. In recent years, there has been a significant increase in cases of personal data abuse in the banking sector, especially concerning fraudulent loan applications. This study aims to identify the factors that create a legal vacuum in the protection of victims of data abuse. This research adopts a normative legal methodology aimed at examining various legal regulations in Indonesia related to personal data protection. The findings can serve as a foundation for further research aiming at developing comprehensive legal solutions and enhancing victim support mechanisms.